EU border security in a time of pandemic: Restoring the Schengen regime in the face of old conflicts and new requirements for public health - Raphael Bossong (Stiftung Wissenschaft und Politik (SWP), 2020)
The massive mobility restrictions in the Schengen zone that were imposed to control the Corona pandemic are to be lifted from mid-June onwards. If a second wave of infections does not follow suit, the German EU Council Presidency may oversee the end of all remaining internal border controls. The reform of the Schengen regulation, which has been overdue since the migration crisis, can be relaunched. The link between secure external borders and internal freedom of movement should have already been reappraised. Looking forward, targeted checks on persons for reasons of public health must be better coordinated. The forthcoming EU pact on migration and asylum will be even more difficult to agree on, however. Access to asylum procedures must be guaranteed without fail, despite national responsibility for public health.
Keywords: 320